Subrecent pollen assemblages of bottom sediments on the south of the European part of Russia - Dyuzhova, Kristina (Ecological Questions, 2017)
This paper presents the new data of the study of subrecent pollen assemblages of bottom sediments on the south of the European part of Russia. Pollen analysis of the forest-steppe and the north steppe zones assemblages have shown that trees pollen reached about 50% of the pollen spectra. Arboreal pollen was represented by Pinus, Betula, Alnus and Salix and broad-leaved trees such as Quercus, Ulmus, Tilia. Pollen analysis of southern steppe zone – seabed deposits of the Sea of Azov and the Tsimlyansk reservoir have shown that herbaceous pollen (up to 80-90% in some sites) was dominated mainly by Chenopodiaceae in pollen assemblages. According to the results obtained from forest-steppe and steppe zones, compositions of pollen assemblages of seabed the Sea of Azov and the Don River deposits represents the modern steppe vegetation.